Implementasi Kurikulum Berbasis Cinta dalam Pembentukan Karakter Peserta Didik di Madrasah Ibtidaiyah - Moh Adib Kamali; Ari Susetiyo; Affan Haekal (TARBAWIYAT, 2025)
The Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) is an educational approach that emphasizes the values of compassion, empathy, and respect for students in the learning process. This approach is relevant for implementation in Madrasah Ibtidaiyah, which are oriented not only toward academic achievement but also toward character building from an early age. This article aims to examine the implementation of the Love-Based Curriculum in shaping students' character in Madrasah Ibtidaiyah, including its concepts, application, the role of teachers, as well as the challenges and strategies for its optimization. The method used in this study is library research, analyzing various literature related to the Love-Based Curriculum and character education, including books, scientific journals, and other supporting documents published within the last ten years. The findings indicate that the implementation of the Love-Based Curriculum can create a more humanistic learning environment and contribute positively to the development of students' character, such as empathy, responsibility, and discipline. However, its implementation faces several challenges, including teacher readiness, administrative burdens, and the diversity of students' characters. These challenges can be addressed through teacher training, strengthening school culture, and integrating the values of love into both instructional and non-instructional activities. Thus, the Love-Based Curriculum plays an important role in supporting character education in Madrasah Ibtidaiyah, while offering an alternative educational approach that is more humanistic and oriented toward the sustainable formation of students' noble character.